2021
DOI: 10.1002/ange.202110589
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming Inactive Lithium with a Triiodide/Iodide Redox Couple for Practical Lithium Metal Batteries

Abstract: High-energy-density lithium (Li)m etal batteries suffer from as hort lifespan owing to apparently ceaseless inactive Li accumulation, which is accompanied by the consumption of electrolyte and active Li reservoir,s eriously deteriorating the cyclability of batteries.H erein, at riiodide/ iodide (I 3 À /I À )redox couple initiated by stannic iodide (SnI 4 )is demonstrated to reclaim inactive Li. The reduction of I 3 À converts inactive Li into soluble LiI, which then diffuses to the cathode side.T he oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The above rejuvenation mechanism has been extensively exploited to enhance the long-term reversibility of lithium-metal anodes. 173,256,257 In addition, SEI stability can be improved by forming a Li 3 N-rich SEI through the rejuvenation of Li 2 O, which is unavoidably generated by the decomposition of LiNO 3 (LiNO 3 + 8Li + + 8e − → Li 3 N + 3Li 2 O). 103,258 This allows the formation of SEIs with superb ionic conductivity due to the increased content of highly ion-conductive Li 3 N (∼10 −3 S cm −1 ) and enables epitaxy-like planar lithium deposition on lithium-metal anodes, thereby enhancing SEI stability.…”
Section: Design Rules For Desirable Seis On Silicon and Lithium-metal...mentioning
confidence: 99%
“…The above rejuvenation mechanism has been extensively exploited to enhance the long-term reversibility of lithium-metal anodes. 173,256,257 In addition, SEI stability can be improved by forming a Li 3 N-rich SEI through the rejuvenation of Li 2 O, which is unavoidably generated by the decomposition of LiNO 3 (LiNO 3 + 8Li + + 8e − → Li 3 N + 3Li 2 O). 103,258 This allows the formation of SEIs with superb ionic conductivity due to the increased content of highly ion-conductive Li 3 N (∼10 −3 S cm −1 ) and enables epitaxy-like planar lithium deposition on lithium-metal anodes, thereby enhancing SEI stability.…”
Section: Design Rules For Desirable Seis On Silicon and Lithium-metal...mentioning
confidence: 99%
“…Moreover, it has been demonstrated that stannic iodide can not only reactivate inactive lithium but also mitigate the corrosion caused by I 3 À on active lithium. [46] These approaches effectively rejuvenate electrochemically inactive lithium in both the inactive SEI and electrically "isolated lithium" metal debris. The I 3 À additive spontaneously removes inactive lithium sources, resulting in the formation of soluble LiI and IO 3 À species.…”
Section: Redox Mediatorsmentioning
confidence: 99%
“…7,8 Many strategies have been developed to mitigate Li dendrite formation and improve the performance of Li-metal batteries, including construction of an articial SEI, 9-13 modication of a separator, [14][15][16] designing novel current collectors [17][18][19][20] and tuning the composition of the electrolyte. [21][22][23] Among them, constructing three-dimensional (3D) electrodes is an effective approach to homogenize Li ion ux, prevent Li dendrite growth and improve the stability of Li-metal batteries. The 3D electrode structure can regulate the kinetics of Li deposition, such as shortening the transport path of Li ions, preventing charge accumulation, and promoting the uniform nucleation and growth of Li metal.…”
Section: Introductionmentioning
confidence: 99%